Immunomodulatory role of vitamin D and selenium supplementation in newly diagnosed Graves’ disease patients during methimazole treatment - Gallo, Daniela; Bruno, Antonino; Gallazzi, Matteo; Cattaneo, Simona Antonia Maria; Veronesi, Giovanni; Genoni, Angelo; Tanda, Maria Laura; Bartalena, Luigi; Passi, Alberto; Piantanida, Eliana; Mortara, Lorenzo (Frontiers in Endocrinology, 2023)
Methimazole (MMI) represents the conventional therapeutic agent for Graves' disease (GD) hyperthyroidism, but MMI efficacy is limited since it marginally affects the underlying autoimmune process. In a previous study, we randomly assigned 42 newly diagnosed GD patients with insufficient vitamin D (VitD) and selenium (Se) levels to treatment with MMI alone (standard) or combined with selenomethionine and cholecalciferol (intervention), and observed a prompter resolution of hyperthyroidism in the intervention group. Here, we aimed to explore changes in peripheral T regulatory (Treg) and natural killer (NK) cell frequency, NK cell subset distribution and function, during treatment. At baseline, circulating total CD3-CD56+NK cells and CD56brightCD16low NK cells were significantly higher in GD patients than in healthy controls (HC) (15.7±9.6% vs 9.9±5.6%, p=0.001; 12.2±10.3% vs 7.3±4.1%, p=0.02, respectively); no differences emerged in Treg cell frequency. Frequencies of total NK cells and CD56brightCD16low NK cells expressing the activation marker CD69 were significantly higher in patients than in HC, while total NK cells and CD56dimCD16+ NK cells expressing CD161 were significantly lower. When co-cultured with the K562 target cell, NK cells from patients had a significantly lower degranulation ability compared to HC (p<0.001). Following 6 months of treatment, NK cells decreased in both groups, but significantly more in the intervention group (total NK: -10.3%, CI 95% -15.8; -4.8% vs -3.6%, CI 95% -9; 1.8%, p=0.09 and CD56brightCD16 low NK cells: -6.5%, CI 95% -10.1; -3 vs -0.9 %, CI 95% -4.4; 2%, p=0.03). Compared to baseline, CD69+ NK cells significantly decreased, while degranulation ability slightly improved, although no differences emerged between the two treatment groups. Compared to baseline, Treg cell frequency increased exclusively in the intervention group (+1.1%, CI 95% 0.4; 1.7%). This pilot study suggested that VitD and Se supplementation in GD patients receiving MMI treatment modulates Treg and NK cell frequency, favoring a more pronounced reduction of NK cells and the increase of Treg cells compared to MMI alone. Even if further studies are needed, it is possible to speculate that this immunomodulatory action might have facilitated the prompter and better control of hyperthyroidism in the supplemented group observed in the previous study.